Laying the Groundwork for a Fatwa on Autism and Marriage: A Conceptual and Legal Exploration in the Malaysian Context - Dahaman, Mohd Akram; Ibrahim, Basri; Cusairi, Rafidah Mohamad (Al-Ahwal: Jurnal Hukum Keluarga Islam, 2025)
As individuals with autism mature, they eventually reach the age for marriage, influenced by biological desires or cultural practices. In Islamic jurisprudence, autism is linked to the concept of `awarid ahliyyah (legal capacity impediments), which refers to obstacles to legal capacity, whether due to natural conditions such as insanity, idiocy, or forgetfulness, or from human factors like ignorance." In the context of the marriage of an autistic person, it is fundamentally subject to the essential pillars of marriage itself. Meanwhile, from the point of view of Islamic family law in Malaysia, it is fundamentally subject to the acts and enactments applied to normal Muslim. The research, utilizing descriptive, inductive, and deductive thematic analysis of library data, concludes that the marriage of an autistic individual is valid, though it may not be ideal, as it fulfills the essential pillar of marriage. In the Malaysian context, Islamic family law applies the same rules to autistic individuals as it does to others, requiring medical expert opinions to assess cognitive capacity. Thus, the opinion of medical experts is crucial in determining the type of autism and the individual’s cognitive capacity. If autism does not impair cognitive ability, autistic individuals can form households like any other couple. This aligns with the objectives of the 2007 Disabled Persons Policy, which ensures equal rights and opportunities for the disabled to participate fully in society. [Ketika individu dengan autisme tumbuh dewasa, mereka akan mencapai usia pernikahan, baik karena dorongan biologis maupun praktik budaya. Dalam kerangka hukum Islam, autisme sering dikaitkan dengan konsep ʿawāriḍ al-ahliyyah, yaitu hambatan terhadap kelayakan atau keabsahan seseorang untuk bertindak secara hukum, baik disebabkan oleh faktor alami seperti kegilaan, kebodohan, atau lupa, maupun oleh faktor manusia seperti ketidaktahuan. Dalam konteks pernikahan individu autistik, penilaiannya tetap bergantung pada rukun nikah itu sendiri. Dari perspektif hukum keluarga Islam di Malaysia, status pernikahan tersebut pada dasarnya tunduk pada undang-undang dan peraturan yang berlaku bagi individu Muslim pada umumnya. Kajian ini menggunakan metode analisis tematik secara deskriptif, induktif, dan deduktif terhadap data kepustakaan. Pernikahan individu autistik sah secara hukum Islam, meskipun mungkin tidak ideal, karena tetap memenuhi rukun dasar pernikahan. Dalam konteks Malaysia, hukum keluarga Islam memberlakukan ketentuan yang sama terhadap individu autistik seperti terhadap individu lainnya, dengan syarat adanya pendapat dari ahli medis untuk menilai kemampuan kognitif mereka. Oleh karena itu, pandangan ahli medis sangat penting dalam menentukan jenis autisme dan tingkat kemampuan kognitif seseorang. Apabila autisme tidak memengaruhi kemampuan kognitif, maka individu autistik berhak dan mampu membangun rumah tangga seperti pasangan lainnya. Hal ini sejalan dengan tujuan Kebijakan Penyandang Disabilitas 2007, yang menjamin hak dan kesempatan yang sama bagi penyandang disabilitas untuk berpartisipasi secara penuh dalam masyarakat.]